Retrofitting masonry infill walls with textile reinforced mortar - Vasconcelos, Graça (2012)
The vulnerability of unreinforced masonry walls (URM) under seismic events, causing huge loss of money and human lives, has revealed the enormous need for an efficient strengthening material. In this context, the present paper reports the development of a new reinforcing material for masonry walls based on braided fibrous structures. These fibrous materials were developed through braiding of polyester yarns around a core made of either glass or carbon fiber (core reinforced braid) or without any core (simple braid). Masonry walls were fabricated by placing these braided materials on the surface of clay brick walls in a mesh like configuration and covering with a mortar layer. The flexural behavior of developed masonry walls was compared with URM and walls reinforced with more commonly used glass fiber laminates using the same configuration and process.